MANAGEMENT OF THE ECONOMIC POWER OF BUSINESS ACTIVITIES AND ITS IMPACT ON ITS EFFICIENCY (Journal of Pharmaceutical Negative Results, 2022)
With the development of small business and entrepreneurship, certain difficulties arise in its activities. They need to effectively use their economic potential. The article discusses the use of economic potential in business, analyzes unused opportunities and develops directions for effective use. The ways of effective use of the economic potential are determined.